The role of management accounting in the successful implementation of strategy and its impact on leverage and performance / Wee Shu Hui ...[et al.] - Wee, Shu Hui; Thirumanickam, Nagarethnam; Abdul Rahman, Ibrahim Kamal; Omar, Normah; Sulaiman, Suzana (2009)
This case study examines the use of a management accounting system (MAS) in the implementation of the company's business strategy to run its business. This particular pharmaceutical company was chosen for the case study because it won the award for "the application of the most effective management accounting system, tool or technique that has had a positive impact on daily practice. This application may have led to quality or process improvement, improved efficiency, lowered costs, or otherwise addressed a particular problem in the workplace." Many companies have problems executing their strategies leading to the realization of lower financial and non-financial performance. The study investigates how this company used management accounting as a tool to align itself with the overall corporate strategic objectives. lt also investigates the strategies involving the use of different financial leverage which affects the performance of this company.